2006
DOI: 10.1002/bit.20896
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of biological nutrient removal (BNR) processes with sedimentation and membrane‐based separation

Abstract: A membrane-enhanced biological phosphorus removal (MEBPR) process was operated in parallel with a conventional EBPR (CEBPR) process under challenging operating conditions to uncover fundamental differences in their ability to remove chemical oxygen demand (COD), nitrogen (N), and phosphorus (P) from municipal wastewater. Both systems exhibited the same potential to achieve excellent soluble-P removal when a favorable COD to P ratio was maintained in the influent. The MEBPR train generated a superior effluent q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 43 publications
3
28
0
1
Order By: Relevance
“…The comparison of sludge production in UCT-type MBR system is shown on Figure 7. Average sludge production for Mode 1, 2 and 3 was 0.28, 0.38 and 0.39 g VSS/g COD, respectively which was similar to other researchers (Lesjean et al 2003;Ramphao et al 2004;Monti et al 2006;Toit et al 2007). Although operating MLSS of lab unit was higher than BNR activated sludge, the characteristics of sludge production in UCT-type lab MBR is similar to other BNR activated sludge.…”
Section: Sludge Productionsupporting
confidence: 89%
See 1 more Smart Citation
“…The comparison of sludge production in UCT-type MBR system is shown on Figure 7. Average sludge production for Mode 1, 2 and 3 was 0.28, 0.38 and 0.39 g VSS/g COD, respectively which was similar to other researchers (Lesjean et al 2003;Ramphao et al 2004;Monti et al 2006;Toit et al 2007). Although operating MLSS of lab unit was higher than BNR activated sludge, the characteristics of sludge production in UCT-type lab MBR is similar to other BNR activated sludge.…”
Section: Sludge Productionsupporting
confidence: 89%
“…Recent investigations (Lesjean et al 2003(Lesjean et al , 2005Ramphao et al 2004;Monti et al 2006;Toit et al 2007) on the modification of MBR have shown that the biological removal of both N and P was successfully achieved with anaerobic-anoxic-oxic process trains with high solids concentrations. In UCT-like modification of MBR, the membrane unit was principally used as a replacement of settling tank.…”
Section: Introductionmentioning
confidence: 98%
“…Some studies reported the good phosphorus removal performance (around 70% removal efficiency) even with poor condition of low F/M and long SRT [13,14,20,21]. Others showed the high P-removal efficiency of above 90% with a sufficient organic loading of above 300 mgCOD/L [17,18,31]. The value in parentheses is a standard deviation It seems that the organic loading rate, characteristics of feed (VFA/TP ratio), and carbon source type are still important factors on biological P-removal even in a MBR [32].…”
Section: Resultsmentioning
confidence: 93%
“…The high P-removal of more than 70% was achieved even with the long solids retention time (SRT) of 72 days without any external carbon sources. Adam et al [15] and Patel et al [16] reported the successful EBPR with the modified MBR systems with the SRT of 20 days and with a high ratio of short chain volatile fatty acids (VFAs) to total phosphorus in the feed [17]. Lesjean et al [18] installed a sidestream membrane unit combined with a University of Cape Town (UCT) process in a pilot plant scale, which provided anaerobic, anoxic, post-anoxic and aerobic stages, consecutively, in a separated reactor with a two-way internal recycle; one was from the anoxic to the anaerobic reactor, and the other from the aerobic to the post-anoxic reactor.…”
Section: Introductionmentioning
confidence: 98%
“…Table 4 shows survey results regarding the use of MBR in combination with known conventional BNR systems. Some of these were the works of Zhang et al (2009), Kim & Nakhla (2009), Khor et al (2006), and Monti et al (2006). It is well known that the prolongation of SRT in MBR lowers the sludge yield (Khor et al 2006).…”
Section: Sludge Reductionmentioning
confidence: 98%